2019
DOI: 10.3390/ijms20133219
|View full text |Cite
|
Sign up to set email alerts
|

Salt Inducible Kinase Signaling Networks: Implications for Acute Kidney Injury and Therapeutic Potential

Abstract: A number of signal transduction pathways are activated during Acute Kidney Injury (AKI). Of particular interest is the Salt Inducible Kinase (SIK) signaling network, and its effects on the Renal Proximal Tubule (RPT), one of the primary targets of injury in AKI. The SIK1 network is activated in the RPT following an increase in intracellular Na+ (Na+in), resulting in an increase in Na,K-ATPase activity, in addition to the phosphorylation of Class IIa Histone Deacetylases (HDACs). In addition, activated SIKs rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…A recent report has demonstrated that SIK inhibitors such as HG-9-91-01 in osteoclast precursors suppress RANKL-induced activation of nuclear factor of activated T cell c1 (NFATc1) and c-Fos, subsequently suppressing osteoclast differentiation and function [91]. Furthermore, SIK has been reported to contribute to glucose and lipid metabolism [92]. Considering these reports, SIK may be considered as a novel therapeutic target for osteoporosis and lifestyle-related diseases.…”
Section: Wnt Signaling and Bone Formationmentioning
confidence: 99%
“…A recent report has demonstrated that SIK inhibitors such as HG-9-91-01 in osteoclast precursors suppress RANKL-induced activation of nuclear factor of activated T cell c1 (NFATc1) and c-Fos, subsequently suppressing osteoclast differentiation and function [91]. Furthermore, SIK has been reported to contribute to glucose and lipid metabolism [92]. Considering these reports, SIK may be considered as a novel therapeutic target for osteoporosis and lifestyle-related diseases.…”
Section: Wnt Signaling and Bone Formationmentioning
confidence: 99%
“… 11 SIK2 overexpression has been implicated in the development of chronic inflammatory diseases, 12 gastric cancer, 13 , 14 and acute kidney injury. 15 Hence, it is an appealing pharmacological target for the treatment of macrophage-driven diseases. 10 , 11 , 13 , 16 19 …”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue covers research articles that investigated the molecular mechanisms of inflammation [1][2][3] and injury [4,5] during different renal pathologies and renal regeneration [6], diagnostics using new biomarkers [7][8][9], and the effects of different stimuli like medication or bacterial components on isolated renal cells or in vivo models [10][11][12], all of which were summarized in a very simplified manner. Furthermore, this Special Issue contains important reviews that dealt with the current knowledge of cell death and regeneration [13,14], inflammation [15][16][17][18], and the molecular mechanisms of kidney diseases [19][20][21][22]. In addition, the potential of cell-based therapy approaches that use mesenchymal stromal/stem cells (MSCs) or their derivates is summarized [23][24][25].…”
mentioning
confidence: 99%
“…Very interesting and new approaches shed a light on the role of non-coding RNAs, either in the progression of glomerular or tubulointerstitial kidney diseases [20] or as new therapeutic targets or biomarkers for fibrotic changes [29]. Another interesting work reviewed the involvement of salt-inducible signal transduction pathways in AKI and discussed the possibility of new therapy options [22].…”
mentioning
confidence: 99%